Autoria e “originalidade” no design gráfico a partir da análise dos discursos do plágio na Internet - Zago, Ana Márcia (2013)
This dissertation aims to investigate the discursive practices disseminated on the Internet about authorship and plagiarism in graphic design, having as corpus newspaper reports and comments about three plagiarism cases, with national and international repercussion from 2010 to 2011, namely: Happy Drive campaign, created by Africa advertising agency in order to promote Grand Vitara, Suzuki (2010); the visual signature developed to represent the Olimpíadas Rio-2016 (2010/2011); and the "official" illustration created in honor of entrepreneur Steve Jobs, ex-CEO and founder of Apple, for his death (2011). The theoretical methodology is the French Discourse Analysis, which choice occurred due to the fact that it focuses on the discourses investigation from the historical, social and ideological analysis involving the subjects, considering the discursive events and the knowledge and power relationships that guide societies and manifest themselves in the language. In addition, it allows to understand the authorship as a complex phenomenon that plays important roles within certain discourses. This work is based mainly on the thinking of Michel Pêcheux and Michel Foucault, and the analyzes therein contained, in an analytic-comparative order, intend, therefore, to allow to understand which meaning effects emanate from the selected discursive practices. This work will also verify how the mass media, particularly the Internet, have important roles in the issue of plagiarism, since providing access to the publication, circulation and appropriation of content (lawfully or not), to promote the matting of discoursive practices that can contribute to improving the institutional discourses, even to outlining the relationship between knowledge and power able of controlling the discourse and/or to determine the "paternity" of creations. The results promote a reflection on the authorship and originality concepts in graphic design and reveal that the relationship between knowledge and power in this professional area, are sometimes determined by the "will to truth" emanating from the institutional discourses, or by the power relations emanating from discursive practices on the Internet, especially those arising from the bonds of affinity and identity established between subjects. Keywords: discourse analysis; authorship; plagiarism; graphic design.